State of The Art Review of Graduate Teacher Education Researches: Relevance to The National Research Priorities of National Higher Education Research Agenda-II - Vannessa D. Umali (Jurnal Studi Pemerintahan, 2020)
The state of the art review assesses the graduate research outputs in education produced by graduate teacher education students in selected public and private schools in the National Capital Region, Philippines during the School Year 2007-2016 based on national research priorities of National Higher Education Research Agenda-II. To provide a means of evaluating existing programs and to validate the result of the state of the art review of graduate education outputs – an expert validation was made among the Research and Development Directors from three (3) institutions of Polytechnic University of the Philippines (PUP), Eulogio "Amang" Rodriguez Institute of Science and Technology (EARIST), and Manuel L. Quezon University (MLQU). Methods are identifying, classifying, and examining the content of data and how it responds according to research priorities set by NHERA-II. The majority of research output in both master's and doctoral studies is attributed to private institutions and already responds to the call to develop research knowledge among higher learning institutions. Nonetheless, the last decades have shown that the task of adopting higher standards is neithereasy nor evident. As a result, the need to evaluate the research priorities has increased. Higher education institutions should prompt the dynamics of social development and lead the society towards a better future (Goksu, A., & Goksu, G., 2015).